Struktur Modal Bank Syariah di Indonesia: Faktor-Faktor yang Mempengaruhinya - Dodi Dodi (Pusat Riset dan Inovasi Nasional, 2023)
The banking capital structure by manage appropriately for smooth operations. This study purposes to: analyze the effect of Profitability, Growth Bank, Bank size on the capital structure of Sharia banks in Indonesia. Assess the size effect of Profitability, Bank size, Growth Bank on the capital structure of Sharia banks in Indonesia. The research method used descriptive and verification. Data is obtain from the published Sharia Bank annual financial statement.Sample of this study is 33 Sharia Banks in Indonesia. Data analysis techniques used panel using the program Eviews 9 fixed effect models. The results showed the profitability and Bank Size are negative effect on the structure of Sharia Bank Capital in Indonesia. Growth Bank have no effect on the structure of Islāmic Bank Capital in Indonesia